TANGGUNG JAWAB PELAKU USAHA TERHADAP PENJUALAN PRODUK YANG MENGALAMI KERUSAKAN PADA KEMASAN DI KABUPATEN BENGKAYANG - NIM. A1011201050, TESSA FRANSA (Fakultas Hukum Universitas Tanjungpura, 2024)
Abstract The rapit development of the times has brought changes in the world of economics. The large number of products circulating in society sometimes do not meet the requirements and standars regulated in this law as proven by the fact that business actors are still found marketing or selling products that have damage to the packaging, meaning that the actions of business actors are inconsistent with and contrary to the protection law consumer. Packaging as made by business actors aims to protect the product so that it damege to the packaging it wil cause the product in the packaging to become damaged and this will be detrimental to consumers. The purpose of this researsh is to determine the responsibility of business actors fors selling product that have damage to the packaging and to find out the efforts made by government to business actors regarding the sale of products that have damage to the packaging. The method used in this research is empirical wit analytical descriptive research specifications. Data was obtained through document study, interviews and observation. The data analysis method used is a qualitative data analysis method. Based on the research results, business actors have so far paid little attention to the packaging of their products, namely that there is no packaging, but the responsibilities given are quite in accordanse with statutory regulations, namely providing campensations in the form of goods. In the form of replacement of a product of a similar or equal value and withdrawal of the product. Is no longger suitable for sale. Apart from that, the government